Assessment of Chitosan-Rue (Ruta graveolens L.) Essential Oil-Based Coatings on Refrigerated Cape Gooseberry (Physalis peruviana L.) Quality (2020)
Cape gooseberry (Physalis peruviana L.) is one of the main exotic fruits in demand throughout the world market. However, this fruit has problems with physical and microbial decay causing losses up to thirty percent during post-harvest stage and market storage. As an alternative for conservation, technologies based on edible coatings of biopolymers incorporating essential oils have been developed. In this paper we studied the e ect of edible coatings based on chitosan (CS) and Ruta graveolens L. essential oil (RGEO) at di erent concentrations applied on the surface gooseberries at 18 2 C. The emulsions exhibited a reduction in the viscosity and the particle size with the increasing in the RGEO amount (from 124.7 cP to 26.0 cP for CS + RGEO 0.5% and CS + RGEO 1.5%, respectively). A lower weight loss was obtained for fruits coated with CS + RGEO 0.5% (12.7%) as compared to the uncoated (15%), while the maturity index increased in a lower amount for CS + RGEO coated than the uncoated fruits. The mesophyll growth was delayed three days after the coating applications for CS + RGEO 1.0% and 1.5%. At day twelve of the coating process, fruits with CS + RGEO 1.5% presented only 3.1 Log UFC/g of aerobic mesophylls and 2.9 Log UFC/g of molds and yeasts, while the uncoated fruits presented 4.2 Log UFC/g of aerobic mesophylls and 4.0 Log UFC/g of molds and yeasts, demonstrating a microbial barrier of the coatings incorporating RGEO in a concentration dependent manner. The CS + RGEO coating also preserve the antioxidant property of case gooseberries after twelve days of treatment under storage according to the 2,20-Diphenyl-1-picrylhydrazyl (DPPH) and 2,20-azinobis-(3-ethyl-benzothiazoline-6-sulphonic acid) (ABTS) results. It was demonstrated by the ABTS method that T5 antioxidant capacity from day one to day twelve only decreases from 55% to 44%, while in the uncoated fruits (T1) the antioxidant capacity decreased from 65% to 18%. On the other hand, using the DPPH method the reduction was from 73% to 24% for the uncoated samples and 55% to 43% for T5. From the sensorial analysis, we recommend the use of CS + RGEO 0.5% that was still accepted by the panelists after the sixth day of application. These results show the potential application of these coatings as postharvest treatment under storage and low temperature conditions during twelve days of treatment for cape gooseberry fruits.